Exploring NFT Business Models as a Pillar of Digital Entrepreneurship Innovation in the Creative Economy Sector - Nurhayaty, Maria (Marqcha Institute, 2025)
The development of blockchain technology and the adoption of Non-Fungible Tokens (NFTs) have created new opportunities for digital creative entrepreneurs to generate economic value based on unique digital assets. However, the use of NFTs in entrepreneurial practices in the creative sector still faces various obstacles, such as unclear adaptive business models, low technological literacy, and a lack of strategic frameworks that can be widely implemented. This study aims to develop a relevant and applicable NFT-based business model for digital creative entrepreneurship. Qualitative research methods were employed using an exploratory case study approach, involving in-depth interviews with digital creative entrepreneurs who have or are potentially integrating NFTs into their business strategies. Data analysis was conducted using thematic analysis techniques to identify patterns and key variables that influence the success of NFT adoption in business models. The results of the study indicate that an effective business model includes four main stages: digital value creation, distribution through NFT platforms, blockchain-based monetization mechanisms, and digital community management. The implications of this research suggest that NFT adoption can enhance monetization opportunities, strengthen relationships with user communities, and expand market reach for creative entrepreneurs. These findings contribute theoretically to the development of digital entrepreneurship literature and practically to the development of business strategies based on new technologies in the digital economy era.